Workshop Pembuatan Engsel Sederhana Menggunakan Mesin Bubut Bagi Mahasiswa di Growth Centre LLDIKTI Wilayah - I - Idris, Muhammad; Iswandi, Iswandi; Amelia, Wan Rizca; Harahap, Uun Novalia (IRA Jurnal Pengabdian Kepada Masyarakat (IRAJPKM), 2023)
This workshop aims to teach students understanding and practical skills in making simple hinges using a lathe. A hinge is a mechanical device used to connect two objects to allow rotational movement around a certain axis. Through practical training, students will learn about the basic principles of lathes, selecting the right materials, precision measurements, and the correct working techniques in manufacturing simple hinges. This workshop will focus on practical steps, from reading technical drawings to the final stages of completion. Participants will be guided by instructors in lathe operations and manufacturing techniques so that they can develop valuable practical skills for the industrial world. By attending this workshop, students are expected to be able to apply the knowledge gained to engineering-based projects, broaden their technical horizons, and gain a competitive advantage in future career competitions.